LQ-PI Controller Design Forfor Multi-Phase Interleaved DC/DC Converter - Joung, Houng-Kun; Kim, Chang-Hyun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Generally, the performance of multi-phase interleaved DC/DC Converter requires the system to be controlled by a power semiconductor with a rated capacity smaller than the conventional converter because the output load current is distributed. However, the controller design of a power semiconductor for the converter is intricate and complicated. In this paper, we propose the optimal control techniques in order to minimize the stress of converters and improve the time response and performance of the controlled system. Methods/Statistical analysis: The proposed control method is to determine the weighting factors of the optimal linear quadratic-proportional integral control in order to meet the specifications of the controlled response, ensuring the internal stability. The mathematical model of the multi-phase interleaved DC/DC Converter is derived using a transfer function according to the relation between input current and output voltage. Findings: The proposed controller has the characteristics of a simpler and improved frequency domain loop shapes than conventional optimal control techniques that achieve internal stability and meet design specifications for good command followings and disturbance reduction against sensor noises and modelling errors. Improvements/Applications: The proposed control method has the advantage to improve the performance of multi-phase interleaved DC/DC converter and guarantee the internal stability and robustness of the controlled response based on the derived mathematical model. The proposed design process is simple and applicable to various industries such as renewable energy and fast charge system for electric vehicles.